Regulation of Rab5 isoforms by transcriptional and post‐transcriptional mechanisms in yeast. Issue 18 (24th August 2017) - Schmidt, Oliver; Weyer, Yannick; Fink, Matthias J.; Müller, Martin; Weys, Sabine; Bindreither, Marietta; Teis, David
Abstract : Rab5 GTPases are master regulators of early endosome biogenesis and transport. The genome of Saccharomyces cerevisiae encodes three Rab5 proteins: Vps21, the major isoform, Ypt52 and Ypt53. Here, we show that Vps21 is the most abundant Rab5 protein and Ypt53 is the least abundant. In stressed cells, Ypt53 levels increase but never exceed that of Vps21. Its induction requires the transcription factors Crz1 and Gis1. In growing cells, the expression of Ypt53 is suppressed by post‐transcriptional mechanisms mediated by the untranslated regions of the YPT53 mRNA. Based on genetic experiments, these sequences appear to stimulate deadenylation, Pat1‐activated decapping and Xrn1‐mediated mRNA degradation. Once this regulation is bypassed, Ypt53 protein levels surpass Vps21, and Ypt53 is sufficient to maintain endosomal function and cell growth.